2020
DOI: 10.1101/2020.09.10.289512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infrared thermography cannot be used to approximate core body temperature in wild primates

Abstract: Understanding the physiological processes that underpin primate performance is key if we are to assess how a primate might respond when navigating new and changing environments. Given the connection between an animal’s ability to thermoregulate and the changing demands of its thermal environment, increasing attention is being devoted to the study of thermoregulatory processes as a means to assess primate performance. Infrared thermography can be used to record the body surface temperatures of free-ranging anim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Indeed, it has been shown that non-human primates and humans tend to spontaneously give birth mostly during the night and early morning (Honnebier and Nathanielsz, 1994;Martin et al, 2018;Macfarlane et al, 2019;Declercq et al, 2023). The nocturnal onset of childbirth might be more temperature efficient (McFarland et al, 2022), free from insects and diurnal predators, and surrounded by more supporting conspecifics, despite vulnerability to nocturnal predators. Thus, activities that promote cohesion and deter predators decreasing pain, danger and anxiety would greatly benefit human childbirth; musical pain, activities seem to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that non-human primates and humans tend to spontaneously give birth mostly during the night and early morning (Honnebier and Nathanielsz, 1994;Martin et al, 2018;Macfarlane et al, 2019;Declercq et al, 2023). The nocturnal onset of childbirth might be more temperature efficient (McFarland et al, 2022), free from insects and diurnal predators, and surrounded by more supporting conspecifics, despite vulnerability to nocturnal predators. Thus, activities that promote cohesion and deter predators decreasing pain, danger and anxiety would greatly benefit human childbirth; musical pain, activities seem to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Since both groups showed similar exposure, the difference in C-SC skin temperature between groups is likely to be due to the suit worn. Because of a positive association between surface and core body [31], it seems a reasonable assumption to consider that C-SC skin temperature reflects core body temperature patterns, but not necessarily absolute core temperature [32]. Then, as a conclusion, compared to wetsuits, it would be logical to assume that dry suit better preserve core temperature as this condition is associated with both an increase of C-SC skin temperature and an alleged increased core-to-skin temperature gradient.…”
Section: Discussionmentioning
confidence: 99%
“…All data used in the current analyses are openly available on Figshare at https://doi.org/10.6084/m9.figshare.25053314 (McFarland et al., 2024).…”
Section: Data Availability Statementmentioning
confidence: 99%